Image, Touch, Possibilities: A Photograph from the 2013 Bulgarian Protests Travels the World - Tomov, Valentina (Anthropologica, 2022)
This paper follows the lives of a photograph, which captured an unlikely gesture amidst a scene of injury during the 2013 mass protests in Bulgaria. It tracks the image’s impacts by focusing on six different registers: the ethnographer, the photographer, the girl in the photograph, a blogger and participant in the protests, global image-sharing sites, and a Hollywood production. The writing strives toward an attunement with the affective force of the image and toward making visible some of the ways it manages to disrupt and reconfigure existing worlds, brighten atmospheres and lives, and create desire and anticipation for a world-in-common.